Q nekotorych woprosach tak. nazw. perekljuczenija kodow pri bilingwizmie i dwokodowosti - MIKLUS, Michal (Wydawcnictwo Naukowe UAM, 1994)
Based on theory of information, psycholinguistics, sociolinguistics, methodology of teaching languages, and neurophysiology, the author of the presentation touches upon a whole number of important topics related to code coupling with bilingualism and dual code performance. Beginning with the problem of the correctly and incorrectly expressed and appercepted speech through a brief analysis of the so-called foreign accent and its types to fundamental bilinguistic types of codes or systems, the author explains some partial and optimal cases of the so-called code coupling also as the sources of inteference and the so-called foreign accent or foreign prosodic feature in generating speech in a foreign language.